Analisis Faktor-Faktor yang Mempengaruhi Produktivitas Tenaga Kerja Wanita Sebagai Pengepul Squin Secara Putting Out - Maja, Onesimus Yulianus; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 1, November 2012 (pp. 1-60), 2012)
This study aimed to determine the effect of independent variables ie, work experience, education level, age, and number of household dependents to the dependent variable, labor productivity of women as collectors squin in Dalung village and to determine which variable is the most dominant influence on the dependent variable. Number of samples is 84 people. Once the data is collected and the analyzed using multiple linear regression analys is with F test and t test at significance level of 5 percent. The test results showed the independent variables significantly influence either simultaneously orpartially. To determine which variables are the most dominant influence on the dependent variable used Standardized Coefficient Beta test. As a result, education level variables that have the most dominant effect on labor productivity of women.
Keywords: productivity; puttingout; the garment industry; women workers